DEVELOPMENT OF A SEAMLESS FİLE SHARİNG (SEAFİSH) APPLİCATİON USİNG OBJECT RELATİONSHİP IN SOCİAL INTERNET OF THİNGS (SIOT) ENVİRONMENT - S.Selvaraj, R.Thangarajan, A.Varmitha, S.Vidhya ,A.Velliyangiri (International Journal of Advanced Science and Technology, 2020)
Internet of Things (IoT) is based on the interaction among smart objects. The development ofInternet of Things relationships between smart objects leads to Social Internet of Things (SIoT) inwhich issues like scalable, navigable and reliability ubiquitous in IoT are determined. This hypothesisis based on utilization of the relationship among objects make use of the social networking notion.Diverse relationships come out among object or smart devices in IoT are listed as Parental, CoLocation, Co-Work, Ownership and Social Object Relationship. In this paper we mainly focus onSocial Object Relationship (SOR) between devices within a social group. We developmed a SeamlessFile Sharing (SeaFiSh) application using object relationship concept in SıoT. It dictates dataexchange between sources and destinations, and as well as development of algorithms such as ViolaJones (VJ) and Local Binary Patterns (LBP) for efficient results along with socket programming andOpenCV module in Python